Substance Abuse Among Blacks Across the Diaspora. (28th July 2016) - Lacey, Krim K.; Mouzon, Dawne M.; Govia, Ishtar O.; Matusko, Niki; Forsythe-Brown, Ivy; Abelson, Jamie M.; Jackson, James S.
ABSTRACT: Background : Lower rates of substance abuse are found among Black Americans compared to Whites, but little is known about differences in substance abuse across ethnic groups within the black population. Objectives : We examined prevalence rates of substance abuse among Blacks across three geographic regions (US, Jamaica, Guyana). The study also sought to ascertain whether length of time, national context and major depressive episodes (MDE) were associated with substance abuse. Methods : We utilized three different data sources based upon probability samples collected in three different countries. The samples included 3, 570 African Americans and 1, 621 US Caribbean Black adults from the 2001–2003 National Survey of American Life (NSAL). An additional 1, 142 Guyanese Blacks and 1, 176 Jamaican Blacks living in the Caribbean region were included from the 2005 NSAL replication extension study, Family Connections Across Generations and Nations (FCGN) . Mental disorders were based upon DSM-IV criteria. For the analysis, we used descriptive statistics, chi-square, and multivariate logistic regression analytic procedures. Results : Prevalence of substance abuse varied by national context, with higher rates among Blacks within the United States compared to the Caribbean region. Rates of substance abuse were lower overall for women, but differ across cohorts by nativity and length of time in the United States, and in association with major depressive episode. Conclusions : The study highlights the need for further examination of how substance abuse disparities between US-based and Caribbean-based populations may become manifested.